The powers of preservation : new life for urban historic places - Moore, Arthur Cotton, 1935- (New York : McGraw-Hill, 1998)
This book is about: Adaptation; Restoration; Preparing for downtowns; ...
Keywords: Architecture; Buildings; Conservation and restoration; Remodeling for other use; Architecture -- Conservation and restoration -- Washington (D.C.); Buildings -- Remodeling for other use -- Washington (D.C.); Architecture -- Conservation and restoration -- United States; Buildings -- Remodeling for other use -- United States